ANALISIS UNSUR INTRINSIK DAN NILAI MORAL DALAM CERPEN “MENGAPA ORANG GILA MEMBUNUH USTAZ?” KARYA FARIS ALFAISAL PADA SURAT KABAR REPUBLIKA EDISI 1 APRIL 2018 - Solihin Nugraha; Jepi Supriatna Suhendra; Diena San Fauziya (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
This research aims to (1) describe the congruence between the intrinsic elements of the short story “mengapa orang gila membunuh ustaz?” by Faris Alfaisal, and (2) to describe the moral value in the short story. This research was analyzed using qualitative method with descriptive approach. The short story “mengapa orang gila membunuh ustaz?” Faris Alfaisal work was researched through data collection steps; (1) reading the short story “mengapa orang gila membunuh ustaz?” intensively, (2) analyzing the intrinsic link between short stories and describing it, then (3) analyzing the moral elements that the author wishes to convey to the short story and describing it. After going through the process of research structural analysis and moral values, can be seen Faris Alfaisal combine the interinsic elements of the short story well, so that the moral massage contained in the short story can be up to the reader of them: wise in understanding every news, no intimidation against any religious leaders, and strengthen ukhuwah/ unity in the community.